CIRI IDENTIK BANGSA PADA IMPLEMENTASI TANDA TANGAN DIGITAL DALAM DOKUMEN ELEKTRONIK - Purwadi; Arujisaputra, Erwin Teguh (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
The authenticity of a nation is identified through one of the most fundamental instruments. Its authentic form is stated in the form of a signature. This short stroke that symbolizes personal identity is a unique form that is unique and only owned by each citizen of the nation. Along with the development of the era, the affixing of signatures on a digital basis has become an obstacle, considering the differences in the platforms used, in other words, initially the affixing of signatures using manual-conventional methods must now switch to digital form. Along with this, this study aims to determine the implementation of digital signatures in electronic documents to guarantee authenticity, data integrity, and non-repudiation in electronic transactions. Through a cryptographic approach, especially asymmetric encryption and one-way hash functions such as SHA and MD5, digital signatures function as legal evidence to replace manual signatures in digital communication. The method used is qualitative-descriptive with a literature study approach and theoretical study. The results show that digital signatures are not only more secure than manual signatures, but also increase efficiency and legal certainty in digital documentation systems.